2021
DOI: 10.1140/epjc/s10052-021-09549-z
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order generalized uncertainty principle corrections to the Jeans mass

Abstract: The Jeans instability is regarded as an important tool for analyzing the dynamics of a self-gravitating system. However, this theory is challenging since astronomical observation data show some Bok globules, whose masses are less than the Jeans mass and still have stars or at least undergo the star formation process. To explain this problem, we investigate the effects of the higher-order generalized uncertainty principle on the Jeans mass of the collapsing molecular cloud. The results in this paper show that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 69 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…Due to the efforts of the researchers, the theoretical value of nebula collapse mass (Jeans mass) was put forward in the literature [9]. However, [9,10] show that the modified Jeans mass based on the generalized uncertainty principle (GUP) is smaller than the original condition, which is consistent with the conclusion that the observed value is smaller than the theoretical value.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Due to the efforts of the researchers, the theoretical value of nebula collapse mass (Jeans mass) was put forward in the literature [9]. However, [9,10] show that the modified Jeans mass based on the generalized uncertainty principle (GUP) is smaller than the original condition, which is consistent with the conclusion that the observed value is smaller than the theoretical value.…”
Section: Introductionmentioning
confidence: 82%
“…In addition, people have done more in-depth research and proposed different expressions of the GUP model based on HUP. At present, studies have shown that [10,20,21], combining the GUP with thermodynamics, the modification of Jeans mass is achieved, and the results show that GUP can reduce Jeans mass. For example, the literature [9,10] explores the Jeans mass using the generalized and extended uncertainty principles and the higher-order GUP, respectively, and the Friedmann equation derived from Gauss-born gravity was used to modify the area law of entropy by GUP to realize the pair Jeans mass amendment in [10].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This indicates the bound of GUP parameter is depended on the its model, and the high-order terms O (β 0 ) have an inportant impact on the effect of QG. Recently, many higher-order GUP [39][40][41][42][43] and extended uncertainty principle models [65,66] have been proposed. By combining them with baryon asymmetry could help us have a deeper understanding of the Universe and QG.…”
Section: Discussionmentioning
confidence: 99%
“…This heuristic work of Pedram is considered as an important step towards establishing a physically reasonable theory of QG. Therefore, many studies have converged on the construction and application of high-order GUP [39][40][41][42]. Recently, according to the commutator [x, p] = i 1 − 2βp 2 , Petruzziello [43] constructed a new higher-order GUP, viz.…”
Section: Introductionmentioning
confidence: 99%